MOBILIZING FOR OR AGAINST THE STATE: STATE FORMATION AND CIVIL WAR IN FOUR WEST AFRICAN STATES - Kurz, Christof. (2017)
Abstract: This dissertation proposes a new way of looking at the causal relationship between state capacity and the outbreak of civil war in post-colonial states by addressing key weaknesses in the current literature on the topic. It makes two main arguments. First, it conceptualizes civil war as a contest between the state and insurgents for the mobilization of support and argues that a state's mobilizational capacity can be seen as a repertoire of three dimensions - symbolic, organizational, and material - with the symbolic and organizational dimensions carrying more weight than the material aspect. States that score higher on at least two dimensions are better able to respond to violent challenges than those with lower scores. Second, it suggests that contemporary post-colonial states' mobilizational capacity has its origins during a critical juncture at the founding moment of the modern state in the late colonial period. Two historical variables - a broad or narrow popular base and the institutions of rural control at independence - critically shaped the evolution of states' mobilizational capacity. These variables led to more inclusive or exclusive mobilizational dynamics, which, albeit weakened, still influence state leaders' contemporary mobilizational capacity through path-dependent processes. The study addresses a series of previously unresolved questions about the causal relationship between state capacity and the onset of civil war: What distinguishes generally weak states that have experienced civil war from other weak states that have responded successfully to armed challenges and prevented civil wars? What aspects of state capacity matter in determining states' ability to prevent civil war? What are the mechanisms that link these key dimensions of state capacity to the outbreak of civil war? And what are the historical origins of states' capacity to fend off armed challenges?; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Peter Uvin.; Committee: H. Zeynep Bulutgil, and Alex de Waal.; Keywords: International relations, Political science, and African studies.